Differential pericyte pathology in the human retina and brain in diabetes mellitus and Alzheimer’s disease - Bakker-van Bugnum, Noëlle; Croes, Aïcha A.; Prevaes, Eva; van Noorden, Cornelis J. F.; Schlingemann, Reinier O.; Klaassen, Ingeborg (Frontiers in Neuroscience, 2026)
IntroductionIn diabetic retinopathy, pericyte dysfunction, pericyte loss, and inner blood–retinal barrier (iBRB) dysfunction contribute to neurovascular unit (NVU) impairment. Diabetes mellitus (DM) is also associated with increased risk of Alzheimer’s disease (AD), and it has been hypothesized that DM-induced NVU impairment in brain capillaries, including pericyte dysfunction, may contribute to AD pathogenesis. In the present hypothesis-generating explorative study, we investigated pericyte characteristics in the iBRB in patients with type 2 DM with or without diabetic retinopathy (DR), and in the blood–brain barrier (BBB) in type 2 DM and AD.MethodsWe analysed human retina and brain samples from controls and donors with DM and/or AD. Immunofluorescence staining for NG2, PDGFRβ, and αSMA was performed to analyse pericyte marker expression, vascular staining coverage, and pericyte cellular density on capillaries.ResultsIn control retina and brain, the average pericyte staining coverage of capillaries was 70–80% based on NG2 and PDGFRβ expression, but only 25% when based on αSMA expression. Pericyte densities were 7 and 9 pericytes/mm capillary length in the control retina and brain, respectively. DM and DR retinas showed marked density reductions to 4 pericytes/mm capillary length. In DM without DR, retinal vascular staining coverage of NG2 and PDGFRβ decreased to 50–56%. In DR retinas, vascular coverage based on NG2 staining was comparable to controls, whereas coverage based on PDGFRβ staining was significantly reduced to 45%. Such reductions were not observed in brain samples from donors with DM or AD; however, NG2 staining was reduced in all patient groups. Both NG2 and PDGFRβ staining were markedly reduced in brain samples from donors with both DM and AD.DiscussionThese trends suggest a specific pericyte pathology in the brain in cases of DM and AD, particularly in patients with both conditions, which differs from the well-characterized pericyte loss observed in the diabetic retina.